Mechanized and individualized application of N-P-K in combined operations in sugarcane - Carneiro, Franciele M. [UNESP]; Furlani, Carlos E.A. [UNESP]; Gírio, Lucas A. da S. [UNESP]; da Silva, Rouverson P. [UNESP]; Malheiros, Euclides B. [UNESP] (FapUNIFESP (SciELO), 2017)
A new concept of fertilizer machine is under development and shows as differential individually fertilizer application, that is sources of N, P and K are applied separately for the purpose of improving the distribution efficiency of the quantities applied. The aim was to compare the quality of the individualized mechanized distribution of N, P and K in combined operations with and without herbicide application, as well as to evaluate the fertilizer application on each side of the fertilizer machine. The experiment was carried out on Cascavel farm, in the municipality of Matão-SP. The experimental design was established according to the criteria of quality control, and variables monitoring carried out in the place during fertilization operation, having the fertilizer distribution operation; simultaneous operation of fertilizer distribution and herbicide application treatments; and two simple operations, fertilizer distribution followed by herbicide application. We concluded that the better operational quality was in two distinct operations. The right side of the fertilizer had the best result because it applied the amount close to the regulated dosage. The distribution of potassium chloride expressed in the control charts greater operational quality compared to other fertilizers.
Keywords: Fertilizer; Fertilizer machine; Operational quality; Statistical process control